2019
DOI: 10.3233/prm-170504
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of patients with cerebral palsy undergoing scoliosis surgery: Survey of surgeon practices

Abstract: PURPOSE: Progressive scoliosis significantly impacts the quality of life in patients with cerebral palsy (CP). Spinal fusion is the mainstay of treatment of progressive spinal curves. The current study aims to identify approaches used by pediatric spine surgeons to optimize care of patients with CP undergoing scoliosis surgery. METHODS: A 33-question survey was distributed electronically to 181 POSNA/SRS members with an established interest in pediatric spinal deformity surgery. Eighty one responses were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…They found that receiving total parenteral nutrition was associated with a lower risk of postoperative infectious complications. Belthur et al 33 studied the surgeon practice related to preoperative optimization for patients with cerebral palsy undergoing corrective spine surgery and found that 97% of responders identified nutrition status as a risk factor that should be optimized, yet the timing and strategy of optimization varied. Specific to the investigated population for this systematic review, Xu et al 34 evaluated a multimodal nutritional management plan in patients undergoing lumbar instrumented fusion surgery.…”
Section: Strength Of Recommendation: Grade Insufficientmentioning
confidence: 99%
“…They found that receiving total parenteral nutrition was associated with a lower risk of postoperative infectious complications. Belthur et al 33 studied the surgeon practice related to preoperative optimization for patients with cerebral palsy undergoing corrective spine surgery and found that 97% of responders identified nutrition status as a risk factor that should be optimized, yet the timing and strategy of optimization varied. Specific to the investigated population for this systematic review, Xu et al 34 evaluated a multimodal nutritional management plan in patients undergoing lumbar instrumented fusion surgery.…”
Section: Strength Of Recommendation: Grade Insufficientmentioning
confidence: 99%
“…Poor nutritional status is common (46% to 90%) in children with cerebral palsy and known to be associated with postoperative infection after scoliosis surgery. [30][31][32][33] Specific risk factors include patients with gastrostomy tube dependence, serum albumin <3.5mg/mL, and total lymphocyte count <1500 cells/mL. 34,35 In our study, cachexia was an independent risk factor for 90-day readmissions, which included surgical site infections.…”
Section: Discussionmentioning
confidence: 65%
“…Preoperative nutritional assessment was also a BPG in 2013 but only reached consensus when using BMI percentile for age in the current BPG 24. This was because of the conflicting evidence on the value of other surveyed measures such as nutritionist referrals and blood tests (albumin/prealbumin) 34–37. It is important to note that different values of BMI percentile for age may be applicable to different patient populations, and this was not captured in the current BPG.…”
Section: Discussionmentioning
confidence: 99%
“…24 This was because of the conflicting evidence on the value of other surveyed measures such as nutritionist referrals and blood tests (albumin/prealbumin). [34][35][36][37] It is important to note that different values of BMI percentile for age may be applicable to different patient populations, and this was not captured in the current BPG. Experts also agreed that a 24-hour only duration of postoperative antibiotic prophylaxis is preferable to prolonged antibiotic coverage.…”
Section: Recommendationmentioning
confidence: 99%